Establishing the added benefit of measuring MMP9 in FOB positive patients as a part of the Wolverhampton colorectal cancer screening programme - Wilson, S; Taskila, T; Ismail, T; Stocken, D; Martin, A; Redman, V; Wakelam, M; Perry, I; Hobbs, R (BioMed Central, 2009)
Background: Bowel cancer is common and a major cause of death. The NHS is currently rolling out a national bowel cancer screening programme that aims to cover the entire population by 2010. The programme will be based on the Faecal Occult Blood test (FOBt) that reduces mortality from colon cancer by 16%. However, FOB testing has a relatively low positive predictive value, with associated unnecessary cost, risk and anxiety from subsequent investigation, and is unacceptable to a proportion of the target population. Increased levels of an enzyme called matrix metalloproteinase 9 (MMP9) have been found to be associated with colorectal cancer, and this can be measured from a blood sample. MMP9 has potential for detecting those at risk of having colorectal cancer. The aim of this study is to assess whether MMP9 estimation enhances the predictive value of a positive FOBt. Methods and design: FOBt positive people aged 60–69 years attending the Wolverhampton NHS Bowel Cancer Screening Unit and providing consent for colonoscopy will be recruited. Participants will provide a blood sample prior to colonoscopy and permission for collection of the clinical outcome from screening unit records. Multivariate logistic regression analyses will determine the independent factors (patient and disease related, MMP9) associated with the prediction of neoplasia. Discussion: Colorectal cancer is a major cause of morbidity and mortality. Pilot studies have confirmed the feasibility of the national cancer screening programme that is based on FOBt. However, the test has high false positive rates. MMP9 has significant potential as a marker for both adenomas and cancers. This study is to examine whether using MMP9 as an adjunct to FOBt improves the accuracy of screening and reduces the number of false positive tests that cause anxiety and require invasive and potentially harmful investigation.